A literatura e a pintura animada no cinema de Aleksandr Petrov: O Velho e o Mar, A Sereia e O Sonho de um Homem Ridículo - Lima, Francisca Maria de Figuerêdo (2025)
This doctoral thesis is a comparative analysis of the poem The Mermaid (1819) by Alexander Pushkin, the short story The Dream of a Ridiculous Man (1877) by Fyodor Dostoevsky, the novel The Old Man and the Sea (1952) by Ernest Hemingway, and their respective adaptations into experimental animation by Aleksandr Petrov. We question how these films construct the reflective nature of the literary works and point to an experimental work, and we argue that Aleksandr Petrov uses a very individual pictorial animation technique to adapt these stories, so that he brings new perspectives of meaning to them, especially through his montage of transitions between images. The main aim of this thesis is to contribute to the understanding of Petrov's cinema within the field of adaptation studies. As for the specific objectives, we analyze how the director's experimental animation technique is reflected in the process of conceiving and understanding the adaptations; we discuss his creative choices, especially in the construction of characters, settings, and transitions between images; and we highlight how Petrov's adaptations add new perspectives of meaning to the literary works on which they are based. In order to achieve this, firstly we discuss Aleksandr Petrov's cinema, his artistic concepts and, in particular, his animation technique; secondly, we discuss the concepts of adaptation used in the analyses; we also review some notes on experimental animated cinema and cinematographic language. We then analyze the three works in sections that relate each of them to the notions of adaptation proposed by Linda Hutcheon (2013) and Julie Sanders (2006), namely: adaptation as a formal entity or product, adaptation as a process of creation/appropriation, and adaptation as a process of reception. This work is mainly based on the following theorists: Sanders (2006), Stam (2006; 2009; 2013), and Hutcheon (2013), on adaptation; Eisenstein (2002), Martin (2005), Aumont et al. (2012), Graça (2006), Miranda (1971), and Harris et al. (2019), on animated cinema and experimental animation, as well as scholars commenting on Petrov's cinema, such as Bendazzi (2016), and others. With this thesis, we prove that Petrov's cinema is a meticulous and individual work that deserves to be highlighted in this field of study, because with its particularities it creates new forms of construction and meaning in animated images, as well as bringing new perspectives of meaning to the literary works on which it is based.